2013
DOI: 10.1016/j.neuropsychologia.2013.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Learning and switching between stimulus-saccade associations in Parkinson’s disease

Abstract: Making flexible associations between what we see and what we do is important for many everyday tasks. Previous work in patients with focal lesions has shown that the control of saccadic eye movements in such contexts relies on a network of areas in the frontal cerebral cortex. These regions are reciprocally connected with structures in the basal ganglia although the contribution of these sub-cortical structures to oculomotor control in complex tasks is not well understood. We report the performance of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…Feedback‐based associative learning, which involves learning through corrective feedback provided on each trial, has been correlated with striatal dopamine release and function of the basal ganglia . Previous studies have reported that feedback‐based associative learning was impaired in PD patients . However, the impairment in feedback‐based learning in PD is not a universal finding, and many factors could contribute to this variability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Feedback‐based associative learning, which involves learning through corrective feedback provided on each trial, has been correlated with striatal dopamine release and function of the basal ganglia . Previous studies have reported that feedback‐based associative learning was impaired in PD patients . However, the impairment in feedback‐based learning in PD is not a universal finding, and many factors could contribute to this variability.…”
mentioning
confidence: 99%
“…10,11 Previous studies have reported that feedback-based associative learning was impaired in PD patients. 12,13 However, the impairment in feedback-based learning in PD is not a universal finding, and many factors could contribute to this variability. Wilkinson and colleagues did not find a selective impairment in PD in probabilistic feedback-based learning, but reported that there was a significant correlation between disease severity and the impairment in feedback-based learning.…”
mentioning
confidence: 99%
“…In fact, a wealth of evidence indicates that PD patients lack the ability to flexibly switch between cognitive sets as well. 10,[15][16][17][18][19][20][21][22] For example, PD patients are impaired when switching attention between extradimensional stimulus features (eg, from color to shape) of multidimensional stimuli (as in the Wisconsin card sorting test) 15,18,19 as well as between welllearned cognitive task-sets. 10,16,17,23 Thus, PD patients exhibit robust set switching deficits.…”
mentioning
confidence: 99%
“…Interestingly, the left ventral premotor cortex, which is thought to play an important role in the shared initiation process, is almost identical to the area that forms part of a wider frontal network mediating inhibitory control over stimulus-elicited eye movements, i.e., saccades to cue and saccades to target in the present study (Hodgson et al, 2007), whereas the homologous area in the right ventral premotor cortex is involved in rule task switching (Hodgson et al, 2007, 2013, 2015). …”
Section: Discussionmentioning
confidence: 52%
“…It is known that behavior slows down when switching between controlled and automatic behavior (Cherkasova et al, 2002; Vernet et al, 2009; Weiler and Heath, 2012, 2014; Hodgson et al, 2013, 2015). The effect of saccade intrusions on subsequent voluntary saccades may reflect a similar switching cost: saccades to cue can be considered to represent visually guided saccades to the cue, whereas the ensuing MGS can be considered voluntarily controlled saccades.…”
Section: Discussionmentioning
confidence: 99%